Acute toxicity, bioconcentration, elimination and antioxidant effects of fluralaner in zebrafish, Danio rerio. (January 2018) - Jia, Zhong-Qiang; Liu, Di; Sheng, Cheng-Wang; Casida, John E.; Wang, Chen; Song, Ping-Ping; Chen, Yu-Ming; Han, Zhao-Jun; Zhao, Chun-Qing
Abstract: Fluralaner is a novel isoxazoline insecticide which shows high insecticidal activity against parasitic, sanitary and agricultural pests, but there is little information about the effect of fluralaner on non-target organisms. This study reports the acute toxicity, bioconcentration, elimination and antioxidant response of fluralaner in zebrafish. All LC50 values of fluralaner to zebrafish were higher than 10 mg L −1 at 24, 48, 72 and 96 h. To study the bioconcentration and elimination, the zebrafish were exposed to sub-lethal concentrations of fluralaner (2.00 and 0.20 mg L −1 ) for 15 d and then held 6 d in clean water. The results showed medium BCF of fluralaner with values of 12.06 (48 h) and 21.34 (144 h) after exposure to 2.00 and 0.20 mg L −1 fluralaner, respectively. In the elimination process, a concentration of only 0.113 mg kg −1 was found in zebrafish on the 6th day after removal to clean water. After exposure in 2.00 mg L −1 fluralaner, the enzyme activities of SOD, CAT, and GST, GSH-PX, CarE and content of MDA were measured. Only CAT and CarE activities were significantly regulated and the others stayed at a stable level compared to the control group. Meanwhile, transcriptional expression of CYP1C2, CYP1D1, CYP11A were significantly down-regulated at 12 h exposed to 2.00 mg L −1 of fluralaner. Except CYP1D1, others CYPs were up-regulated at different time during exposure periods. Fluralaner and its formulated product (BRAVECTO ® ) are of low toxicity to zebrafish and are rapidly concentrated in zebrafish and eliminated after exposure in clean water. Antioxidant defense and metabolic systems were involved in the fluralaner-induced toxicity. Among them, the activities of CAT and CarE, and most mRNA expression level of CYPs showed fast response to the sub-lethal concentration of fluralaner, which could be used as a biomarker relevant to the toxicity. Graphical abstract: Highlights: Insecticide fluralaner has low toxicity and medium bioconcentration in zebrafish. CAT and CarE are induced by sub-lethal fluralaner and may be useful as biomarkers. Fluralaner increased some and inhibited other CYP mRNA expression levels.